2019
DOI: 10.5937/ekonsig1902015x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of political risk on foreign direct investment

Abstract: Rezime. Politički rizik kao fenomen posmatran iz perspektive multinacionalnih korporacija koje se javljaju u ulozi nosioca stranih direktnih investicija odnosi se na političke i regulatorne opasnosti koje postoje u zemljama domaćinima. Multinacionalne korporacije posmatraju politički rizik zemlje domaćina kao jednu od najvažnijih odrednica u donošenju investicionih odluka. U tom pogledu, političko okruženje je veoma važno i predstavlja preduslov stabilnog investicionog ambijenta. U manje razvijenim zemljama u … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Finally, in this study, there is a negative relationship between political stability and the level of FDI in developing countries. The influence of political stability is also a negative relationship, as shown in the study of Janaćković & Janaćković (2019), which supports this study. The correlation has shown that corruption is the most common intermediate.…”
Section: Summary Of the Findingssupporting
confidence: 89%
“…Finally, in this study, there is a negative relationship between political stability and the level of FDI in developing countries. The influence of political stability is also a negative relationship, as shown in the study of Janaćković & Janaćković (2019), which supports this study. The correlation has shown that corruption is the most common intermediate.…”
Section: Summary Of the Findingssupporting
confidence: 89%